IMPROVING THE EFFICIENCY OF TRAINING QUALIFIED ATHLETES IN THE ATHLETICS HEPTATHLON - Borovayavru, V.A.; Netsvetaeva, E.S.; Vrublevskiy, E.P.; Sevdalev, S.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to increase the efficiency of training athletes specializing in track and field heptathlon based on the design of key individual biomechanical parameters in individual disciplines. Methods and structure of the study. A decision-making algorithm has been developed for the individualization of the training of qualified athletes specializing in track and field heptathlon. The latter was tested in the training process of the strongest all-around athletes in Belarus, and its effectiveness was assessed by the magnitude of the increase in sports results and indicators in individual all-around disciplines. Results and conclusions. Following the decision-making algorithm when individualizing the training of athletes contributed to the increase in the total amount of the all-around due to the “pulling up” of the lagging disciplines to the indicators of the predicted model. Thus, the sports results of the five athletes who took part in the experiment improved by an average of 6.29%, and the performance in the technical disciplines of the heptathlon by 9.92% compared to the previous year. Particular attention is paid to the development of individual biomechanical model indicators, which serve as the basis for the formation of control training effects aimed at improving the technical training of all-round athletes.